Nitrogen uptake and use by oil palm seedings of various genotypes and gene expression of a nitrogen responsive genotype - Law, Chu Chien (2016)
High economic value of palm oil had gathered much interest for rapid expansion of oil palm plantation in Malaysia. However, most of the soils in Malaysia were generally low in fertility status, hence planting oil palm in these soils could cause further soil degradation and require high Nitrogen (N) fertilizer input in order to maintain high yield output. While fertilizers being the most expensive inputs, increase of application rate would result in increase in production cost as well as introducing negative impact to the environment. To maintain high yield oil palm output with limited soil fertility, effort had been focused on improving oil palm N use efficiencies (NUE). This 3-parts research explore the potential genotypic different of 9 oil palm genotypes which originated from the same high yielding siblings. In part-1, the N uptake performance among selected high yielding oil palm genotypes were quantified. Six-months old and nine-months old oil palm seedlings consist of nine different high yielding genotypes from Sime Darby were cultivated in the glasshouse in a randomized complete block design in split-plots arrangement with four replicates. These oil palms were supplied with ammonium sulphate with 5% atom excess (a.e.) N-15. Destructive sampling was then carried out after 3 months of planting and plant samples were analyzed for total N and N-15 enrichment. Results demonstrated that oil palm at 6 months old did not show any significant difference in N uptake between genotypes either with or without P fertilizer application. However, oil palm at 9 months old demonstrated significant differences between genotypes in total dry matter production and total N uptake. Hence, there was a significant difference in N derived from fertilizer among genotypes. Additionally, oil palms at 9 months old also showed a significant increase in N uptake with P fertilizer application. Genotype A (14/34 ´ 2367/17) demonstrated significantly higher N uptake compared to the other genotypes, except for genotype F (9/103 ´ 2318/17). Part- 2 of this study was aimed to determine the respond of the oil palm during recovery from N stress condition. Another set of same oil palm genotypes were cultivated and modified Cooper solution (without N) was applied to the oil palm genotypes for 6 months until oil palm leaves turned yellow. After that, standard Cooper solution was applied to the oil palm genotypes. The SPAD reading were taken daily from frond number three and leave samples were harvested from frond number three, with interval of 7 days until SPAD reading is stabilized, for total N analysis. All genotypes, with the exception of Genotype I, demonstrated a 9-day lag period before the SPAD reading and the N concentration in the leaves begin to increase. The SPAD reading for Genotype I remained stagnant throughout the whole experimental period. Genotype A showed the fastest recovery ability as compared to the other genotypes. The SPAD readings of the oil palm showed a significant positive association (r = 0.7337) with leaf N concentration with leaf N concentration. Part-3 of this study was to determine the gene expression of superior oil palm prior to N stress condition. Genotype A that exhibits favorable positive response to N was subjected to gene expression analysis study. RNA were extracted from root samples collected during the palms were subjected to N-stress and non N-stress conditions. The root RNA samples were then analyzed using microarray analysis. A total of 105,072 gene probes were used in the microarray and 3 genes that related to oil palm N stress respond were identified to be significantly regulated (p < 0.05; Fold Changes > 1.5 folds): (1) 9-cis-epoxycarotenoid dioxygenase 1, (2) Early nodulin-93, and (3) Cryptochrome-1. Overall, this research demonstrated that genotypic different among oil palms would affect the plant growth and performance. In particular, Genotype A (14/34 ´ 2367/17) used in this study carries had exhibited superiority in N-up taking capability and N-stress tolerance capability. Stagnant period of plant N status prior to N recovery shall also be given attention, as it could greatly alter the management of fertilizer application in oil palm plantations. Genotype A carries the potential gene that could unlock the barrier to breed oil palm genotype which likely to be both high yielding and high NUE. Therefore, further study need to be carried out in order to annotate all possible genes responsible for high NUE, consecutively crossing this gene to the other high yielding oil palm genotypes.